(untitled) (Sciences & Technology. A, exactes sciences, 2006)
This paper suggests an extension of Lai’s results about the first order autoregressive representation of Markov bi-dimensional chain of 1-order. In the case of markov chain with independent components, we find of course the conditions validating these results for each component.